Understanding the seedling development in sedge species (Cyperaceae, Poales) from micromorphological and anatomical perspectives - Silva, Lucimara Reis de Oliveira [UNESP]; Trevisan, Rafael; Oriani, Aline [UNESP] (Elsevier, 2023)
Considering the representativeness and morphological diversity of Cyperaceae in grassland ecosystems, this study aimed to understand the early seedling development in Cyperus sesquiflorus, Lagenocarpus minarum, and Rhynchospora rugosa based on micromorphological and anatomical analyses. One hundred diaspores of each species studied that were collected in natural environments were placed to germinate under controlled conditions and analyzed every 24 h for one month. Samples at different stages of post-seminal development were analyzed under scanning electron microscopy and light microscopy. The final germination percentage was 68%, 36%, and 31%, respectively. Rhynchospora rugosa had the longest mean germination time (17.68 ± 0.99 days). Germination begins with the protrusion of the embryonic axis followed by the coleoptile in L. minarum, whereas in C. sesquiflorus and R. rugosa the coleoptile is the first structure to appear, forming a tubular structure that involves the shoot apical meristem. The shoot and root apical meristems become well-differentiated only after the beginning of germination. The results suggest a correlation between the post-seminal development and the resting embryo morphology. Considering the phylogenetic position of Cyperaceae, Juncaceae, and Thurniaceae within the cyperid clade, the coleoptile is most likely the derived condition in the clade and led to greater protection of the shoot apical meristem and the first plumular leaves in relation to the phaneromeric cotyledon present in Thurniaceae and Juncaceae.
Keywords: Coleoptile; Cotyledon; Cyperids; Germination; Seed; Seedling